Evolution of China's Economy and Monetary Policy: An Empirical Evaluation Using a TVP-VAR Model - Seewon Kim (East Asian Economic Review (EAER), 2021)
China has experienced many structural changes in the process of economic development over the past three decades. Using a time-varying parameter VAR model with stochastic volatility and mixture innovations, this study investigates whether such structural changes in, especially tools and operational aims of monetary policy, affect the monetary transmission mechanism. We find that impulse responses of output growth and inflation to monetary shocks have substantially increased and then reversed to decrease around 2005-2006. This time variation is mainly caused by changes in the monetary transmission mechanism, i.e., the manner in which main macroeconomic variables respond to policy shocks, rather than by changes in volatilities of exogenous shocks. The result implies that aggressive monetary policy to facilitate economic growth in the developing economies may be legitimized, unless it causes inflation seriously.
Keywords: C11; E30; E52; 330; Monetary Policy; Evolution of Transmission Mechanism; Stochastic Volatility; Time-Varying Impulse Responses